In vitro study of 980nm diode laser in dental implant disinfection - Fábio Gonçalves; Artêmio Luiz Zanetti; Raquel Virgínia Zanetti; Saturnino Aparecido Ramalho (Faculdade São Leopoldo Mandic, 2009)
Objective: To evaluate the potential of 980nm diode laser to reduce bacteria after irradiation of three different dental implant surfaces contaminated with Enterococcus faecalis and Porphyromonas gingivalis, as well as the possible changes in the irradiated implant surfaces.Methods: Seventy two implants with machined surfaces, airborne particle abraded with titanium oxide and acid-etched surfaces were exposed to Enterococcus faecalis and Porphyromonas gingivalis cultures and irradiated with 980nm diode laser with power of 2.5 and 3,0W. After laser treatments, the number of remaining colony-forming units was studied and implant surface morphology was analyzed by scanning electron microscopy. Results: The results showed 100% reduction of the bacteria on the implants irradiated with 3.0W. Moreover, 100% reduction of bacteria was also achieved on the implant surfaces contaminated with Porphyromonas gingivalis when irradiated with 2.5W and 3.0W. Bacteria reduction was not complete for the implants contaminated with Enterococcus faecalis, irradiated with 2.5W and surfaces treated with TiO2 airborne particle abrasion (78.6%) and acid etching (49.4%).The scanning electron microscopy analysis showed that at the power settings used, no implant surface changes were found. Conclusion: The 980nm diode laser was effective in decontaminating the Enterococcus faecalis and Porphyromonas gingivalis without promoting surface alteration in the implants.